Natural life cycle and molecular characterization of Taenia talicei Dollfus, 1960 (Cestoda: Taeniidae) from northwestern Patagonia, Argentina - Bagnato, Estefanía (2025)
Through morphological and molecular studies, the natural life cycle of Taenia talicei Dollfus, 1960 (Cestoda: Taeniidae) from Argentine Patagonia is elucidated, involving subterranean rodents (Ctenomyidae) as intermediate hosts, and the Andean fox Lycalopex culpaeus (Canidae) as definitive host. Metacestodes (mono- and polycephalic fimbriocerci) were found mainly in the peritoneal cavity of Ctenomys terraplen, and the strobilate adult in the intestine of L. culpaeus. Correspondence between metacestodes and strobilate adults was based primarily on number, size and shape of rostellar hooks: 45–53 hooks alternated in two rows, small hooks 88–180 μm longand large hooks 230–280 μm long, with the characteristic shape described in the two main description of the species, both that of the metacestode (original description) and that of the strobilate adult (obtained experimentally). Further genetic analysis (cox1 gene mtDNA) corroborated the conspecificity between the metacestodes and the strobilate adults found in the Andean fox in the same study area. Genetic analysis also revealed conspecificity of the taxon found in Patagonia with the species registered in GenBank as T. talicei, obtained from different intermediate and definitive hosts from Peru and Argentina. Taenia talicei was previously reported from Argentina in the form of metacestodes naturally infecting two other species of Ctenomys. However, the strobilate adult was only described from the experimental infection of a domestic dog. Hence, this is the first report of the natural life cycle of T. talicei and of a species of Taenia endemic from South America.